Caracterização da produção agroecológica e da mecanização agrícola em horticultura : um estudo de caso - Nadai, Karla Bethania Ledesma de (2017)
Agroecological agriculture make possible the production of food in a sustainable way, respecting the environment, society and stands out as one of the income alternatives for small farmers for the growing search by the population for healthier food. In Campo Grande - MS, the Family Agriculture Organic Producers Cooperative, made up of 28 families of agroecological producers, is representative in the production and marketing of organic products, serving as a reference for the present study. The main objective of this work was to characterize agroecological production and agricultural mechanization in horticulture at ORGANOCOOP. The information obtained was based on the production system used, characterizing aspects related to ownership, organic management plan, products, organic certification, agricultural operations and the specific needs of agricultural machinery and implements. Therefore, it is important to note that, in order to maintain producers in the organic certification process, public policies, especially in rural extension, are more efficient, that the technology for the production of agro-ecological inputs is being researched and that it is developed or the producer machines and equipment focused on the particular needs of the family agroecological producer.